Biomass Percentage of Organic Soil Layers in The Rasau Jaya Tiga Village - Diah Trismi Harjanti; Fidhi Melia Medhina; Sri Buwono (Jurnal Pendidikan Geografi Gea, 2023)
Peat is a wetland ecosystem characterized by a high accumulation of organic matter with a low decomposition rate. Rasau Jaya Tiga Village is one of the villages in the Rasau Jaya District with peat soil type characteristics of 1,885,478,466.83 m2, which are shallow or thin, and the medium category is 1,825,792,728.85 m2. Therefore it is necessary to do research on the proportion of biomass contained in organic soil layers in the village of Rasau Jaya Tiga with descriptive quantitative research. The sample used is a soil sample. Soil samples were taken to determine peatland biomass using the survey method and the Walkley Black and Dennstedt methods for testing soil samples. The results of testing the soil samples obtained the highest organic carbon content in the A4 C sample (11-20 cm), namely 56.37% and the lowest organic carbon in the E4 sample code (11-20 cm), namely 7.41%, which means that the peat soil content will be released. Organic biomass is the proportion that is contained in organic soil and turns into carbon dioxide (CO2).Keywords: Peat, Peatland, Biomass, Organik Carbon.